Colleges and collegiality: An international imperative - Paul Smith (UN Chronicle, 2014)
The concept of globalization pulsates throughout just about every discussion or article on international relations, the macroeconomy or worldwide social predicaments. The only reason the word hasnt become hackneyed is that its meaning is germane to everything of significance that is happening to our world in this millennium.